Análise experimental de lajes lisas nervuradas de concreto armado com armadura de cisalhamento - SOUZA, Shirley do Socorro Melo de (2007)
Two-way waffle flat slabs are structural elements of reinforced concrete supported directly on columns, under bending moments over the two directions, they improve the speed of the execution and save moulds and concrete and, consequently, labor. This work seeks to contribute for the study of the behavior of this kind of slab, as the shear resistance of the ribs and the punching in the solid area, through tests of 8 two-way reinforced concrete waffle flat slabs. Comparative analyses between the experimental results and estimated by national and international design codes had been carried out. The slabs were square, with 1.800 mm of side and total height of 140 mm. The cross section of the slabs was formed by ribs with 50 mm of width for the base and 100 mm for the upper base and the spaces between the ribs had been filled with EPS blocks (expanded polystyrene). The main variables considered were the type of shear reinforcement in the ribs (trusses, closed vertical stirrup and 45 inclined stirrup) and the use of 45 inclined stirrup as shear reinforcement in the solid region. They were presented and analyzed the results observed for the vertical displacements, deformation in the flexural and shear reinforcement, and the propagation of cracks. The values observed for failure loads were compared with the estimated ones. It was observed that the shear reinforcement in the ribs did not increase the failure loads and that the shear reinforcement in the solid region increased significantly the resistance of the slabs.